Applying the Delphi Approach to Prioritize Social Factors Affecting the Development of Children Under Six Years - Mitra Sadrkhanlou; Ali Maher; Khalil Alimohammadzadeh; Mehrnoosh Jafari; Mohammadkarim Bahadori (BMC, 2023)
Abstract Background Social determinants of health have a key role in the growth and development of children, particularly in early childhood which is mentioned from infancy to the age of six years old. These factors might cause disparities in living conditions and consequently bring about inequities regarding different aspects of development such as emotional, psychological, social, psychological, and intellectual. This research aimed to provide a model for prioritizing social factors affecting the development of children under six years. Methods We used quantitative-qualitative (mixed) method to perform data analysis. The statistical population included 12 medical experts and professionals in the field of children's development and social determinants of health that were selected using the snowball method. In the quantitative section, a Delphi technique was applied to screen the extracted indicators. Then through applying a decision-making trial and evaluation laboratory (DEMATEL) method, the cause-and-effect interactions among main social determinants were identified. To analyze data, super decision software was used. Results According to literature review and the results obtained from focus group discussions, five dimensions including individual factors, family factors, environmental factors, governance, and global factors were identified. Based on the study findings, the criterion of "family factors" was mentioned as the most important priority affecting childhood development. Furthermore, the sub-criterion of "International Programs and Policies" received the greatest priority among other sub-criteria with a profound impact on children's healthy growth and development. Conclusion Despite the current knowledge about social determinants of health, it is required to identify the most influential socioeconomic factors on childhood development. In such a manner, political strategies for improving the health condition of children can be implemented based on scientific evidence. Due to the crucial role of family factors, environmental factors and other socio-economic conditions, health policy makers and public health practitioners should be informed of the importance of these factors in shaping the health condition of children.